The minimum liquidity deficit and the maturity structure of central banks' open market operations: lessons from the financial crisis - Jens Eisenschmidt; Cornelia Holthausen (European Central Bank (ECB), 2010)
This paper studies the relationship between the size of the banking sector's refinancing needs vis-à-vis the central bank and auction rates in its open market operations in times of financial market stress. In a theoretical model, it is found that marginal rates at central bank auctions may increase if the share of troubled banks becomes too high relative to the total size of the banking sector's refinancing needs. An empirical analysis then aims at determining the size of open market operations needed to absorb large stress levels in interbank money markets and hence contain central bank auction rates. Finally, the paper analyses effects of the composition of open market operations of different maturities on auction rates. It is found that a too high share of longer-term refinancing induces a rise in auction rates which is undesirable. Therefore, the analysis suggests that there is a lower bound for the amount of liquidity provided through short-term operations.
Keywords: G01; G10; G21; 330; Central Bank; financial crisis; money market; Open market operations